(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2021)
Зінчук Т.О., Левківський Є.В. КОНВЕРГЕНЦІЯ АГРО-БІЗНЕС-СТРУКТУР В НОВІЙ МОДЕЛІ ГЛОБАЛІЗАЦІЙНОЇ ЕКОНОМІКИ Мета. Аналіз та обґрунтування можливостей адаптації агро-бізнес-структур до ефективної інтеграції, переплетіння економічної діяльності, зближення і об’єднання (конвергенція) їх потенціалів, що сприятиме подоланню соціально-економічних негативних наслідків функціонування вертикально інтегрованих структур холдингового типу та посиленню переваг різних організаційних форм підприємств малого і середнього аграрного бізнесу. Методика дослідження. Методологічною та теоретичною базою дослідження стали теорії та погляди, представлені в працях зарубіжних і вітчизняних вчених. Результати дослідження отримані за допомогою як загальнонаукових, так і спеціальних (економічних) методів наукового пізнання. Загальноісторичний контекст конвергенції розглянуто на основі історичного та діалектичного методу; метод аналізу та синтезу використано при виявленні загальноглобальних проблем на фоні економічної кризи. Аргументація теоретичних положень, які характеризують закономірності становлення конвергенції і зв’язок організаційних форм господарювання в аграрному секторі, сформована на системному аналізі, законах логіки, методі наукової абстракції. Статистичний, табличний та графічний методи було використано для порівняльного аналізу показників ефективності економічної діяльності агропідприємств. Результати дослідження. Виявлено переваги та недоліки існуючих агро-бізнес-структур в умовах нових вимог глобалізації, передбачених наслідків економічної кризи та орієнтації на цілі сталого розвитку, на основі яких формуються об’єктивні умови для процесу конвергенції. Наукова новизна результатів дослідження. Обґрунтовано, що за умови конвергенції різних категорій підприємств забезпечується мінімізація соціально-економічних розбіжностей між ними та нівелюються нерівності при виході на внутрішні і зовнішні ринки. На відміну від існуючих радикальних поглядів щодо виключної шкоди від діяльності агрохолдингів, запропоновано методичний підхід, згідно з яким трансформаційні зміни на основі конвергенції дозволятимуть передбачати і мінімізувати ризики, особливо в малому і середньому агробізнесі, які виникатимуть в період пандемії та економічної кризи. Даний підхід сприятиме згуртуванню форм господарювання в аграрному бізнесі, що відображає досвід найкращих практик господарювання розвинених країн світу. Практична значущість результатів дослідження. Запропоновані наукові ідеї та погляди щодо конвергенції, як процесу зближення та інтеграції потенціалів і ресурсів існуючих форм господарювання, можуть бути використані на рівні підприємств, що забезпечить синергетичний ефект масштабу їх діяльності та відповідність цілям сталого розвитку за умов сприятливого інституційного середовища. Ключові слова: аграрний бізнес, агрохолдинги, глобалізація, інновації, конвергенція, сталий розвиток, форми господарювання аграрних підприємств. Зинчук Т.А., Левковский Е.В. КОНВЕРГЕНЦИЯ АГРО-БИЗНЕС-СТРУКТУР В НОВОЙ МОДЕЛИ ГЛОБАЛИЗИРОВАННОЙ ЭКОНОМИКИ Цель. Анализ и обоснование возможностей адаптации агро-бизнес-структур к эффективной интеграции, переплетению экономической деятельности, сближению и объединению (конвергенции) их потенциалов, что способствует преодолению социально-экономических последствий функционирования вертикально интегрированных структур холдингового типа и усилению преимуществ разных организационных форм предприятий малого и среднего бизнеса. Методика исследования. Методологической и теоретической базой исследования стали теории и взгляды зарубежных и отечественных ученых. Результаты исследования получены с помощью как общенаучных, так и специальных (экономических) методов научного познания. Общеисторический контекст конвергенции рассмотрен на основе исторического и диалектического метода; метод анализа и синтеза использован при выявлении общеглобальных проблем на фоне экономического кризиса. Аргументация теоретических положений, которые характеризуют закономерности становления конвергенции и связь организационных форм хозяйствования в аграрном секторе, сформирована на системном анализе, законах логики, методе научной абстракции. Статистический, табличный и графический методы использовались при сравнительном анализе показателей экономической эффективности деятельности агропредприятий. Результаты исследования. Выявлены преимущества и недостатки существующих агро-бизнес-структур в условиях новых требований глобализации, предвидения последствий экономического кризиса и ориентации на цели устойчивого развития, на основе которых формируются объективные условия для процесса конвергенции Научная новизна результатов исследования. Обосновано, что в условиях конвергенции разных категорий предприятий обеспечивается минимизация социально-экономических разобщений между ними и нивелируются неравномерности при выходе на внутренние и внешние рынки. В отличии от существующих радикальных взглядов касательно исключительного вреда, наносимого деятельностью агрохолдингов, предложен методический подход, согласно которому трансформационные изменения на основе конвергенции позволят предупредить и сократить риски, особенно в малом и среднем агробизнесе в период пандемии и экономических кризисов. Данный подход способствует солидарности форм хозяйствования в аграрном бизнесе, о чем свидетельствуют успешные практики хозяйствования развитых стран мира. Практическая значимость результатов исследования. Изложенные научные идеи и взгляды относительно конвергенции, в качестве процесса сближения и интеграции потенциалов и ресурсов существующих форм хозяйствования, могут быть использованы на уровне предприятий и обеспечивать синергетический эффект масштаба их деятельности в соответствии с целями устойчивого развития при условии благоприятной институциональной среды. Ключевые слова: аграрный бизнес, агрохолдинги, глобализация, инновации, конвергенция, устойчивое развитие, формы хозяйствования аграрных предприятий. Zinchuk T.O., Levkivskyі Ye.V. CONVERGENCE OF AGRO-BUSINESS STRUCTURES IN THE NEW MODEL OF GLOBALIZATION ECONOMY Purpose. The aim of the article is analysis and substantiation of possibilities of adaptation of agro-business structures to effective integration, intertwining of economic activity, convergence and unification (convergence) of their potentials that will promote overcoming of social and economic negative consequences of functioning of vertically integrated structures of holding type and strengthening of advantages of various organizational forms of enterprises small and medium agrarian business. Methodology of research. The methodological and theoretical basis of the study is theories and views presented in the works of foreign and domestic scientists. The results of the study are obtained using both general and special (economic) methods of scientific knowledge. The general historical context of convergence is considered on the basis of the historical and dialectical method; the method of analysis and synthesis is used in identifying global problems against the background of the economic crisis. Argumentation of theoretical provisions that characterize the patterns of convergence and the relationship of organizational forms of management in the agricultural sector, formed on a systematic analysis, the laws of logic, the method of scientific abstraction. Statistical, tabular and graphical methods are used for comparative analysis of economic performance of agricultural enterprises. Findings. The advantages and disadvantages of the existing agro-business structures in the conditions of new requirements of globalization, anticipated consequences of the economic crisis and orientation on the goals of sustainable development, on the basis of which objective conditions for the convergence process are formed, are revealed. Originality. It is substantiated that under the condition of convergence of different categories of enterprises the minimization of social and economic differences between them is ensured and inequalities in entering the domestic and foreign markets are levelled. Contrary to the existing radical views on the exceptional damage from the activities of agricultural holdings, a methodological approach is proposed, according to which transformational changes based on convergence will anticipate and minimize risks, especially in small and medium agribusiness, which will occur during pandemics and economic crisis. This approach will promote the cohesion of forms of management in the agricultural business, which reflects the experience of best management practices of developed countries. Practical value. The proposed scientific ideas and views on convergence, as a process of convergence and integration of potentials and resources of existing forms of management, can be used at the enterprise level, which will ensure a synergistic effect of their scale and compliance with sustainable development goals in a favourable institutional environment. Key words: agrarian business, agro-holdings, globalization, innovations, convergence, sustainable development, forms of management of agrarian enterprises.